Synthesis of four-arms star-shaped PCL-b-PEG as a potential amphiphilic hydrogel / Wafiuddin Ismail ... [et al.] - Ismail, Wafiuddin; Wan Abdul Khodir, Wan Khartini; Abd Hamid, Shafida Abd Hamid; Daik, Rusli (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Hydrogel formulations have drawbacks in delivering hydrophobic drugs which can aJect its effciency. Introducing amphiphilic system into hydrogel can overcome this limitation and increase hydrogel effectiveness as a drug cargo. In this study, four arms star-shaped block copolymers with polyethylene glycol (PEG) as hydrophilic block and polycaprolactone (PCL) as hydrophobic block were synthesized via a combination of ring- opening polymerisation (ROP) and Steglich esterification. The structures were confirmed by 1 H-NMR and FTIR analysis. The polydispersity index (PDI) indices from gas permeation chromatography (GPC) were 1.3 to 1.6, suggesting controlled polymerisation reaction occurred. Average molecular weight analysis, Mn based on 1 H-NMR are close to the theoretical value. However, there is a slight difference of Mn between GPC and proton analysis due to the ability of GPC determining Mn for the star-shaped polymer. Both star-shaped polymers possess high thermal stability (>350 °C) based on thermal decomposition study using TGA analysis. The presence of PEG had increased the hydrophilicity and solubility of the PCL in the hydrogel since an opaque homogeneous formulation form when using the amphiphilic star-shaped polymer. The pH (7.25 ± 0.03) and viscosity (9330 cP) of the formulation are set within the compatibility and suitable for human skin and topical application.